Corporate tax incidence in India - Samiksha Agarwal; Lekha S. Chakraborty (Levy Economics Institute of Bard College, 2017)
The paper attempts to measure the incidence of corporate income tax in India under a general equilibrium setting. Using seemingly uncorrelated regression coefficients and dynamic panel estimates, we tried to analyze both the relative burden of corporate tax borne by capital and labor and the efficiency effects of corporate income tax. The data for the study is compiled from corporate firms listed on the Bombay Stock Exchange (BSE) and the National Stock Exchange of India (NSE) for the period 2000-15. Our empirical estimates suggest that in India capital bears more of the burden of corporate taxes than labor. Though it is contrary to the Harberger (1962) hypothesis that the burden of corporate tax is shifted to labor rather than capital, it confirms the existing empirical results in the context of India.
Keywords: C33; H22; H25; 330; Corporate Tax; Tax Incidence; Capital; Labor